Significance of cultural and historical resources in development of discovering tourism (case of Volodymyr-Volynskyi district of Volyn region) - Netrobchuk, Iryna (Human Geography Journal, 2016)
Twenty attractive historical places are located in Volyn region. They have preserved many monuments of architecture, archeology and history both local and national importance. Volodymyr-Volynskyi district is worthy to be noted among others with many interesting historical inhabited places, historical and cultural objects of the period of Kievan Rus’. On state registration there are 103 objects of cultural heritage (including 20 of national importance). 46 out of 103 are historical monuments (including 2 of national importance), 4 archeological sites, 48 architectural and urban planning (including 18 - of national importance), 3 monuments of monumental art and one monument of landscape art in the Volodymyr-Volynskyi district. There is the State historical and cultural reserve “Ancient Volodymyr” in the city. Tourist image of the area is determined primarily by the presence of cultural and historical resources that can be used in tourism. Have been analyzed and assessed the informative value of 13 subgroups of cultural and historical resources of the Volodymyr-Volynskyi district by the method of S. Kuzyk. 12 out of 13 relate to middle attractive with a factor of discovering value 0.64. Moreover, this result is presented without palace-and-park ensembles. En early slavic and ancient horodysche; mound; sacred monuments of defensive type – Zymne Svyatogorsk monastery of the assumption can be noted as the most interesting objects of excursion routes among archaeological sites. It is worthy of notice the house world musician Stravinsky – historical monument of national importance in the city Ustilug. Sixteen works of his creativity are relevant to “Volyn page”. Works of folk craftsmen and professional artists are popular among tourists. Machonyuk family, V. Onischuk and M. Vavrysevych are well-known masters-embroiderers in original towels. T. Pasievych – a professional master of pysankarstva. T. Romaschuk, Y. Duben’ are craftsmens in basket weaving. Complex component analysis and evaluation of cultural and historical heritage would provide an opportunity for tourist enterprises more fully engage it in order to improve the route of the “Golden diadem of Volyn”. It would be also useful in the development of new local history tour routes to promote local attractions history and culture of his native land.